2020
DOI: 10.1177/0954407020925568
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of driving behaviours of truck drivers using motorway tests

Abstract: Road transportations still play a dominant role in goods delivery, and driving behaviours significantly affect the fuel economy of heavy-duty trucks. Plenty of fossil fuel is wasted as a result of unreasonable driving behaviours even in the case of highly experienced drivers. The objective of this paper is to analyse drivers’ behaviours over two segments of motorways and estimate the potential benefits of fuel saving caused by a change in driving habits during national and international goods delivery. Drivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Also, this indicator has also been reasonably recognized in the driver's awareness. Most of the current studies have confirmed that maintaining a high and stable speed is significantly related to the ecological driving modes [63,65]. (ii) Driven distance (mileage).…”
Section: Other Factors Worth Notingsupporting
confidence: 52%
“…Also, this indicator has also been reasonably recognized in the driver's awareness. Most of the current studies have confirmed that maintaining a high and stable speed is significantly related to the ecological driving modes [63,65]. (ii) Driven distance (mileage).…”
Section: Other Factors Worth Notingsupporting
confidence: 52%
“…In the authors' results, fuel consumption rates over the acceleration range of 1.3 m/s 2 ~1.5 m/s 2 were approximately three time of 0.3 m/s 2 ~0.5 m/s 2 . Gao et al (Gao et al, 2020) indicated that fuel consumption rates depended more on acceleration than speed based on heavy duty trucks over the real driving tests.…”
mentioning
confidence: 99%